Pengembangan Media Pembelajaran ALGEBOX untuk Materi Pengenalan Bentuk Aljabar - Pramesthi Al Kautsari; Fika Widya Pratama (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research includes research and development (R&D) which aims to produce a learning media that can be accessed via a smartphone and contains questions for introductory algebra material aimed at class IX C students at Satya Wacana Christian Junior High School, then test the feasibility, practicality and effectiveness of the learning media that has been developed. Algebra is a subject matter that must be learned at the junior high school level, but students admit that Algebra material is one of the difficult mathematics materials to master. The development model used is the ADDIE development model Analyze, Design, Development, Implementation and Evaluation. This research was conducted on February 5, 2024 even semester of the 2023/2024 school year at Satya Wacana Christian Junior High School. Data were collected through media and material validation sheets, student response questionnaires and teacher response questionnaires, as well as pretests and posttests. The results showed that ALGEBOX learning media had been developed in accordance with ADDIE development procedures. The validity test of ALGEBOX learning media according to material experts 89% and media experts 93% showed valid results. The results of the student response questionnaire 86% and teacher response questionnaire 90%, then it is said to be practical. The effectiveness results are evidenced by the increase in the pretest average of 57.81 to 86.86 on the posttest score and reinforced by the results of Asymp. Sig. (2-tailed) <0.05 so it is said to be effective. It can be concluded that this learning media meets the criteria of validity, practicality and effectiveness.